KEANEKARAGAMAN SATWA BERKHASIAT OBAT DI TAMAN NASIONAL BETUNG KERIHUN, KALIMANTAN BARAT INDONESIA (Diversity of Medicinal Animals in Betung Kerihun National Park, West Kalimantan, Indonesia) - Yohanes AE Putra; Burhanuddin Masy'ud; Maria Ulfah (Media Konservasi, 2008)
This study was carried out to gain data on animal species and their subtances/derivatives believed had medicinal properties that were utilized and traded by local people around Betung Kerihun National Park (BKNP). The study was conducted at the 12 villages around area of BKNP. Snowball method was used to determine respondents. There were 32 respondens interviewed. The data obtained was analysed by using descriptive quantitatively method. The study showed that there were 39 animal species and 19 animal substances/derivatives that utilized as medicinal purposes by local people around BKNP. There were also 9 animal species and 4 animal subtances/derivatives traded by those peoples. Local peopl’s perspectives on animal utilization had been changed from nature to economic orientation. Law enforcement, giving conservation education, involving local peoples on biodiversity conservation management, and introducing captive breeding program to local communities are needed to raise the understanding and awareness of the importance of habitat and animal species conservation in BKNP.Key word: Medicinal Animal, subtances/derivatives, medicinal purposes, utilization, trade, conservation.